2017
DOI: 10.2146/ajhp160168
|View full text |Cite
|
Sign up to set email alerts
|

Successful use of laboratory monitoring to facilitate an invasive procedure for a patient treated with dabigatran

Abstract: Coagulation assay monitoring for dabigatran, with emphasis on an ECA dabigatran concentration of <50 ng/mL, was used to assess safety regarding bleeding risk before a nonemergent surgical procedure in an 86-year-old woman with a right femoral neck fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 11 publications
0
3
0
Order By: Relevance
“…Using a very conservative approach and reporting the only specific intervention in the hip fracture population, Byron et al present a case report in which a patient was delayed for 5 days prior to hemiarthroplasty for her hip fracture. 11 This case does illustrate the impact of renal function as is well established. The patient had a creatinine clearance of 33 mL/min.…”
Section: Discussionmentioning
confidence: 72%
“…Using a very conservative approach and reporting the only specific intervention in the hip fracture population, Byron et al present a case report in which a patient was delayed for 5 days prior to hemiarthroplasty for her hip fracture. 11 This case does illustrate the impact of renal function as is well established. The patient had a creatinine clearance of 33 mL/min.…”
Section: Discussionmentioning
confidence: 72%
“…neuraxial procedure) that require minimal to no anticoagulant effect at the time of the procedure. Indeed, the empirical treatment cessation of 1–3 days before the intervention, as suggested in the EU‐SmPC and in the Food and Drug Administration (FDA) Label Information, revealed plasma concentrations of > 30 ng mL −1 at least for dabigatran etexilate and rivaroxaban . However, a recent prospective multicenter study confirmed that a last DOAC intake 3 days before a procedure resulted in minimal (< 30 ng mL −1 ) pre‐procedural anticoagulant effect for almost all patients.…”
Section: When To Measure Direct Oral Anticoagulants and How To Interpmentioning
confidence: 99%
“…In particular, works on serpent venom are, unarguably, success stories. Some examples are: Batroxobin, a widely used thrombin-like enzyme and commonly extracted from the venom of Bothrops atrox and Bothrops moojeni , has been used as a replacement for thrombin in bleeding injuries 3 ; Ecarin, from Echis carinatus , as the primary reagent for laboratorial tests that monitor anticoagulation 4 ; and Captopril, developed from peptides of the Bothrops jararaca venom, as a widely adopted inhibitor of the angiotensin converting enzyme (ACE). Other examples of venom-derived drugs include: Aggrastat, for myocardial infarct and ischemia; Ancrod, for stroke; Defibrase, for acute cerebral infarction and angina pectoris; Exanta, used as an anti-coagulant; Hemocoagulase, for hemorrhage; and Integrilin, for acute coronary syndrome 5 .…”
Section: Background and Summarymentioning
confidence: 99%